The Role of Education and Training on Employee Career Development at the Aceh Manpower and Population Mobility Service - Ahmad, Lukman; Rizal, Syamsul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
This study aims to determine the role of education on employee career development at the Aceh Manpower and Population Mobility Service. population of employees at the Aceh Manpower and Mobility Department as respondents. The data analyzed in this study is primary data in the form of questionnaire circulation. The data is then processed through multiple linear regression analysis with the help of SPSS. The objects in this study are the facilities, individual abilities, and efforts of the independent variables. performance. The results of this study identify that simultaneously, the variables of Education and Training on the Career Development of Employees at the Aceh Manpower and Population Mobility t-test. The results of the study on the education and training variable (X) obtained tcount = 34,356 while ttable 2,086, the results of this calculation indicate that tcount > ttable with a significance level of 0.000 or the probability is far below = 5%. Thus, the results of statistical calculations show that partially the education and training variables play a significant role in increasing the career development of employees at the Aceh Manpower and Population Mobility Service. Aceh Manpower and Population Mobility Service.